HUBUNGAN KERAPATAN MANGROVE TERHADAP KELIMPAHAN KEPITING BAKAU (Scylla spp.) DI DESA TANJUNG REJO KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Tiur Natalia Manalu; Yunasfi Djayus; Rusdi Leidonald (AQUACOASTMARINE, 2016)
Mud crab is potential mangrove fishery that have important economic value. Tanjung Rejo Village has broad mangrove that used to support society economy causing degradation mud crab habitat. This study aims to know mangrove ecosystems condition in Tanjung Rejo village and analyze mangrove density effect to mud crab abundance. This study held in February until March 2016. Determination sampling using purposive sampling method and divided into 3 stations with different mangrove density condition. This study analyzed is mangrove ecosystem condition, water quality, mud crab population and mangrove density correlation with mud crab abundance. The results show mangrove density condition in Tanjung Rejo village at station 1 highly density category 2433 trees/ha, at station 2 low density category (damaged) 900 trees/ha and at station 3 medium density category 1000 trees/ha. Regression equation of the influence mangrove trees density and mud crab abundance is Y = 389.3 + 0,0348x. The relationship between mangrove density and mud crab abundance correlation coefficient (r) 0.4970.Keywords : Mud Crab Abundance, Mangrove, Tanjung Rejo Village, Correlation